Application of Fracture Barrier Analysis in Well Stimulation Planning for Upper Baturaja Limestone Formation Based on Well Log & Drill Cutting Data from OBF-01 and OBF-04 Wells, Offshore Southeast Sumatra - Aris Buntoro; Muhammad Nurcholis; Basuki Rahmad; Allen Haryanto Lukmana; Ristiyan Ragil Putradianto (Journal of Petroleum and Geothermal Technology, 2020)
In general, the South Sumatra Regional Stratigraphy of the Baturaja Limestone Formation facies is deposited on the Buildup Carbonate (Reef) and the Limestone Clastic Carbonate of the Baturaja Formation which grows as a buildup reef on the platform in the Basement High (Horst) underneath is the Lemat Formation volcanic deposits. Referring to the facies model in general, the Baturaja Limestone Formation, the depositional environment starts from Shelf Lagoon Open Circulation - Winnowed Edge Sand - Organic Buildup - Fore Slope - Deep Shelf Margin - Open Sea Shelf - Basin, meaning that carbonate is formed starting from pure organic Cabonate Buildup Reef without / a little sludge / mud to the Carbonate Basin where more muddy / mud is present, this condition causes clay minerals to also more and more mix with Terigenous Clastics (Quartz, feldpar). The complexity of the Baturaja Limestone Formation requires fracture barrier analysis associated with well stimulation planning in order to increase oil productivity with the appropriate method.   Fracture barrier fracture analysis is an approach method to determine the depth interval that becomes a barrier in hydraulic fracturing by correlating the results of geomechanical analysis from well log data and mineralogical analysis from drill cuttings data, so that a commonly used well stimulation method can be selected, namely hydraulic fracturing, acidizing, and acid-fracturing.From the ternary diagram plot the XRD (bulk) analysis results show that the distribution of the main minerals (Quartz, Clay, Calcite) is more dominant in the ductile zone, hard to frac category. This shows that all the depth intervals in the OBF-01 and OBF-04 wells are more ductile, and are not recommended for hydraulic fracturing. From the XRD (bulk) analysis, Calcite mineral is more dominant, so for well stimulation work it is recommended to use acidizing or acid-fracturing.